O estágio não obrigatório remunerado nos CMEIS de Francisco Beltrão-PR: do ato educativo às relações e condições de trabalho - Bido, Gisele Fernanda Tiburski. (2023)
This dissertation is related to the line of research Culture, Educational Processes and Teacher Training, of the Graduate Program in Education of Francisco Beltrão (PPGEFB) at master's level, at the State University of Western Paraná (UNIOESTE). The theme is part of the field of teacher training, based on studies by the research group “Higher Education, Training and Teaching Work” (GESFORT). In this way, the problem lies in the question: How does the development of paid internships in the CMEIs of Francisco Beltrão-PR imply the formation and relations and conditions of teaching work? From this problematic, it raised as general objective of the research: To make explicit the relations and conditions of work and of formation of the interns that develop non-compulsory remunerated internship in the Municipal Centers of Early Childhood Education (CMEIs) of Francisco Beltrão-PR. The pursuit of this objective surrounds all this work, situating the object/field of study: the noncompulsory paid internship in early childhood education. The research is based on a critical-dialectical approach, using a theoretical framework that made it possible to analyze the research object in its relationship with society. Authors such as Piconez (1991), Pimenta (2001; 2008), Saviani (2009; 2011), Pimenta and Lima (2006; 2008) contributed to understanding the internship in teacher education. To understand the work and professionalization process, Marx (2011), Azzi (2005), Oliveira (2010), among others, were used. As methodological procedures, we opted for bibliographic research, document analysis and field research, using data collection via questionnaires and forms addressed to the directors or pedagogical coordinators of the CMEIs, to the Municipal Secretary of Education (SMEC) and to the interns. It is considered that the non-compulsory paid internship is a type of internship, not mandatory as a curricular component, for high school students, vocational education and undergraduate students interested in acquiring experience in professional practice. The research results point to little production in the area of internship in early childhood education, as well as the legal context and the relationship between internship and teacher training. The data obtained in the field research through the questionnaires and forms sentshowed the development of the non-compulsory paid internship in the CMEIs as a training activity and as a job. Also noteworthy is the internship as an educational act and in relations and working conditions. If, on the one hand, the internship is a formative act, on the other hand, the non-compulsory paid internship is a job immersed in relationships and working conditions that have contemplated the precariousness and professionalization of teachers. The answers obtained contemplated the analysis that reflects the issue of work, professionalization and working conditions. By way of conclusion, it is clear that the interns have been occupying the place of a trained teacher, demonstrating the precariousness and deprofessionalization of teaching work. Thinking about non-compulsory paid internships is a great challenge, as there is a prevalence in dealing with mandatory internships. In this way, the results of the research contribute to thinking about the non-compulsory paid internship in early childhood education, providing the intern with a voice to declare the relationships and working conditions as an element of the internship.